The Role of Young Men's Christian Association in Community Empowerment Through Saul Alinsky's "Human Power" Approach and Its Implications for Community Development in Medan City - Pardede, Piki Darma Kristian; Suryanto , Dwi; Rujiman (Journal of Environmental and Development Studies, 2020)
The purpose of this study was to analyze the empowerment process carried out by the Young Men's Christian Association (YMCA) through the "Human Power" approach and its implications for the development of the city of Medan. In this study carried out using qualitative descriptive and data collection techniques used in this study, namely in- depth interviews (In-depth interview) and documentation. The result obtained were changes in public awareness of economic and educational conditions. The aspect of education, the presence of YMCA in forming Community work with the alternative education program Duta Kasih Club which has encouraged children to continue to get education even with informal channels. Then YMCA as an organizer consisting of young people able to touch the issue of youth in joining and building a business unit or credit union (CU), a global alternative tourism package (GATN) and fostering youth capacity to gain skills (Citizenship Education). Empowerment is not a product but a process that is continually sought to build the quality of life of the community. The development approach asserted by Alinsky puts forward "Human Power" as the power to use human energy, the human spirit, and the ability to realize it to others.